Morphological Study of the Intraorbital Muscles (Musculi Bulbi) in Rat and Guinea Pig - Demirci, Beste; Onuk, Burcu; Tütüncü, Şerife; Gültiken, Murat Erdem (Adnan Menderes University, 2023)
Intraorbital muscles in the human are similar to those in the mammals as regards morphology and function, except for the absence of the retractor bulbi muscle in the human. The aim of this study is to determine the morphological and morphometric features of the eye muscles in the rat and guinea pig used as a model for various studies. Twenty-four bulbus oculi of 12 rats and 32 bulbus oculi of 16 guinea pig were investigated by subgross and histological methods. Certain morphometric data of musculi bulbi were obtained by stereo-microscope. Samples were fixed in 10% formalin for subgross procedures and preserved in Bouin solution for histological methods. The muscular part of the intraorbital muscles in the rat was examined and each muscle was determined to be originated from near the optic foramen and to be attached to sclera close to corneal limbus by tendinous ends. The intraorbital muscles of the guinea pig were relatively weak compared to the body size. The functional part of the intraorbital muscles located around the optic nerve was considerably short and attached to the sclera by the long tendinous ends. Retractor bulbi muscle was small muscle batch located ventrolateral of the optic nerve in rat and substantially weak muscle bundles that envelop the optic nerve in the guinea pig.
Keywords: Hayvansal Üretim (Diğer); Zootechny (Other); Guinea pig; ocular muscles; rat